The Flexural Fatigue Behavior of Honeycomb Sandwich Composites Following Low Velocity Impacts - Solmaz, Murat Yavuz; Topkaya, Tolga (Mdpi, 2020)
Featured Application Authors are encouraged to provide a concise description of the specific application or a potential application of the work. This section is not mandatory. This study experimentally investigated the flexural fatigue behaviors of honeycomb sandwich composites subjected to low velocity impact damage by considering the type and thickness of the face sheet material, the cell size and the core height parameters. Carbon-fiber reinforced composite and the aluminum alloy was used as the face sheet material. First, the static strength of undamaged and damaged specimens was determined by three-point bending loads. Secondly, the fatigue behaviors of the damaged and undamaged specimens were determined. Low velocity impact damage decreased the flexural strength and fatigue lives but increased the damping ratio for all specimens. Maximum damping ratio values were observed on specimens with a aluminum face sheet.
Keywords: honeycomb sandwich composites; flexural test; low velocity impact; fatigue